Nanoelectronics : device physics, fabrication, simulation - Knoch, Joachim (De Gruyter Textbook, 2020)
The author presents all aspects, in theory and experiments, of nanoelectronic devices starting from field-effect transistors and leading to alternative device concepts such as Schottky-barrier MOSFETs and band-to-band tunnel FETs. Latest advances in Nanoelectronics, as ultralow power nanoscale devices and the realization of silicon MOS spin qubits, are discussed and finally a brief introduction into device simulations is given as well.